A Combined Methodology for Landslide Risk Mitigation in Basilicata Region by Using LIDAR Technique and Rockfall Simulation. (31st July 2011) - Colangelo, G.; Guariglia, A.
Abstract : Rockfalls represent a significant geohazards along the SS18 road of Basilicata Region, Italy. The management of these rockfall hazards and the mitigation of the risk require innovative approaches and technologies. This paper discusses a hazard assessment strategy and risk mitigation for rockfalls in a section of SS118, along the coast of Maratea, using LIDAR technique and spatial modelling. Historical rockfall records were used to calibrate the physical characteristics of the rockfall processes. The results of the simulations were used to define the intervention actions and engineering strategy for the mitigation of the phenomena. Within two months, 260 linear meters of high-energy rockfall barriers for impact energies up to 3000 kJ were installed. After that, according to road authority, the SS18 road was opened in a safe condition. The results represent a valid cognitive support to choose the most appropriate technical solution for topography strengthening and an example of good practice for the cooperation between innovative technologies and field emergency management.